Site Measurement and Study of Vertical Freezing Wall Temperatures of a Large-Diameter Shield Tunnel - Jun Hu; Wenbo Liu; Yutao Pan; Hui Zeng (Advances in Civil Engineering)
When a large-diameter shield tunnel boring machine enters or exits a tunnel, the newly exposed tunnel face is prone to instability and water seepage. In order to prevent collapse of the tunnel face, local ground improvement can be used until the permanent tunnel lining can be installed. The tunnel launching project of the Nanjing Metro Line 10 cross-river tunnel had a high stability requirement for the entry and exit phases. To this end, this project used a combination of cement treatment and ground freezing methods. In this project, field measurement of the vertical freezing improvement of the large-diameter shield tunnel was carried out. The temperature distribution and ground surface deformation of the vertical frozen soil wall at the end of the tunnel during the active freezing and maintenance freezing periods were analyzed in detail. The result shows that the surface settlement and seepage were successfully controlled by the combined cement treatment and ground freezing. On the other hand, the combination of cement treatment and ground freezing helps to control the freezing-induced heaving. The hydration heat in improved ground leads to an increase in ground temperature and this leads to additional freezing duration. It was examined that the frozen soil wall and the enclosure structure were in a good cementation condition. These measured values provide guidance on the timing of the shield departure. The project results confirmed that instability and water permeation did not occur in the tunnel face during the subsequent excavation.